Sustainability Constitutionalism: Adopting National Perspectives on Sustainability - Martin, Rhett (Journal of Strategic Innovation and Sustainability, 2024)
The development of environmental constitutional rights has provided important legal advances in procedure, standing, enforcement and remedies for matters concerning environmental protection and conservation. The constitutional textualization of environmental norms represents a significant development in both constitutional and environmental law, as well as providing a powerful impetus for cross-disciplinary research. These developments have not been mirrored to the same extent with sustainability thresholds and practices. Just as environmental rights are a legitimate avenue for constitutional protection, this article argues a similar position should accord to sustainability rights in constitutions by constitutional textualization of sustainability standards and thresholds. Achieving this constitutional recognition ensures sustainability has a national agenda for a sustainable future.